Paisagens construídas pelo olhar do outro: uma análise imagológica do conto "Dois poetas da província", de Milton Hatoum - Clara Glenda Mendes Galdino; Katia Aily Franco de Camargo (Revista Odisséia)
In the short story collection A Cidade Ilhada(2014), Milton Hatoum crafts images that depict cultural interactions between the native population and foreigners within the Amazonian space. This article examines the short story “Dois Poetas da Província”, aiming to describe the representations of Brazil and Manaus in the context of these interactions. The study is grounded in Imagological Theory, as developed by Daniel-Henri Pageaux (2011), who views images as ideological constructs that reveal relationships between cultures. Additionally, we incorporate Michel Collot’s (2012, 2013) concept of landscape, which considers the interplay between space, the observer’s perspective, and the image created. The analysis identifies a structure shaped by alterity, leading to an interpretation of a mania in the Brazilian gaze toward French European culture, alongside a phobia of local culture—rooted in a heteroimage shaped by European stereotypes about Brazil.